TROPOMI aboard Sentinel-5 Precursor: Prospective performance of CH4 retrievals for aerosol and cirrus loaded atmospheres - Butz, André (Remote sensing of environment, 2012)
The TROPOspheric Monitoring Instrument (TROPOMI) will be part of ESA's Sentinel-5 Precursor satellite platform scheduled for launch in late 2014. One of TROPOMI's primary goals will be to accurately monitor methane (CH4) concentrations in the Earth's atmosphere by measuring spectra of sunlight backscattered by the Earth's surface and atmosphere in the shortwave-infrared (SWIR) spectral range. Absorption by CH4 along the lightpath allows for the spectroscopic retrieval of its atmospheric abundance given accurate knowledge of the lightpath. Scattering by aerosol and cirrus particles, however, can modify the lightpath substantially causing retrieval errors if not appropriately taken into account. We propose and evaluate a method to minimise these errors by simultaneously retrieving CH4 total column concentrations and scattering properties of the atmosphere. The method exploits observations by TROPOMI's SWIR and near-infrared (NIR) channels and is based on a parameterisation of particle amount, height distribution, and microphysical properties. Retrieval performance is tested for a trial ensemble of simulated observations that cover a realistic range of aerosol and cirrus loaded scenes. For more than 90% of the trials, residual scattering induced CH4 errors are less than 1%. Retrievals with residual errors larger than 1% and non-convergent retrievals typically occur for difficult scenes with high particle load or very small surface albedo.
Die Zahl "4" ist im Titel tiefergestellt
Gesehen am 20.12.2018